THE FISHERY OF NAGARJUNASAGAR, ON THE RIVER KRISHNA, DURING 1976-80. - Ramakrishnaiah, M (Indian Journal of Fisheries, 2011)
The fishery of Nagarjunasagar reservoir during 1976-80 is presented. P. pangasius, M. aor, S. childreni and L. fimbriatus, species native to the river Krishna, formed the mainstay of the fishery. There has been a shift in the relative abundance between carps and catfishes, the former dominating during the earlier period and the latter during the later period. The probable reasons for the low fish productivity have been indicated.